STRATEGI KOMUNIKASI DIGITAL MARKETING PARIWISATA DI MASA PANDEMI COVID-19 (STUDI KASUS WISATA MANDALIKA, LOMBOK, NUSA TENGGARA BARAT) - Simatupang, Yunita (WELL-BEING: Journal of Social Welfare, 2022)
Tourism communication is something that must be owned by every tourism industry for regular and organized tourist activities. With good tourism communication, it can help and serve the needs of the community. We need a mature strategy and a neat, effective and efficient plan so that the success rate increases and the risk of failure shrinks. This research aims to find out the digital marketing communication strategy of tourism in the time of the covid-19 pandemic. The theory used in this research is the marketing communication mix theory, The research method used is a kulaitative research method with a case study approach. This method of data collection is by in-depth interviews to travel service providers, as well as conducting observations and documentation. The results of tourism communication research with digital strategies built by Mandalika tourism services, Lombok using aspects of advertising, personal selling, sales promotion, direct marketing, public relations and WOM show a link between each other and in accordance with the target of tourist services to social media. The important role of digital marketing strategy in the process of conveying information about covid-19 is also prioritized by service providers (travel), in order to increase public tourism interest through the content provided, in order to be useful for tourists.